Pengaruh Pembelajaran Filsafat Pancasila terhadap Pemahaman Nilai-Nilai Pancasila pada Mahasiswa - Cahya Lesmana; Prima Melati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effectiveness of the Philosophy of Pancasila course in improving students’ understanding and implementation of Pancasila values. The study is motivated by the importance of the Philosophy of Pancasila course in shaping students’ character, morality, and national awareness amidst globalization and increasingly complex social challenges. This research employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews with six students, consisting of three students currently taking the Philosophy of Pancasila course and three students who had completed the course. The data analysis technique used the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. The results showed that most students had a good understanding of Pancasila values after participating in the Philosophy of Pancasila course. Students understood Pancasila not only as the state ideology but also as a guideline for social, national, and civic life. In addition, the Philosophy of Pancasila course had a positive influence on students’ attitudes of tolerance, social awareness, democratic behavior, and respect for differing opinions. However, the implementation of Pancasila values still faces challenges, particularly the influence of social media and individualistic culture. Therefore, it is necessary to develop more contextual and applicable learning methods so that students can implement Pancasila values in their daily lives